The Management of Cardiometabolic Risk in MAFLD: Therapeutic Strategies to Modulate Deranged Metabolism and Cholesterol Levels - Annalisa Pezzoli; Ludovico Abenavoli; Marialaura Scarcella; Carlo Rasetti; Gianluca Svegliati Baroni; Jan Tack; Emidio Scarpellini (Medicina)
Background and Objectives: Fatty Liver Disease is a major health problem worldwide. We can distinguish liver steatosis as non-associated or associated with chronic/acute alcohol consumption. These two entities share similar stages ranging from hepatic fat storage (namely, steatosis) to inflammation, necrosis, and fibrosis until hepatocellular carcinoma (HCC). Over time, “Metabolic Associated Fatty Liver Disease” (MAFLD) has replaced nonalcoholic fatty liver disease (NAFLD) nomenclature and has included cardiometabolic criteria in these patients definition. Thus, obesity, type 2 diabetes mellitus (T2DM), hypertension, and dyslipidemia are MAFLD features and are of the metabolic syndrome. Importantly, there is not a specific treatment for MAFLD, but there are therapeutic strategies that act on metabolic dysfunction related to MAFLD. They can reduce the progression of liver fibrosis and its complications. Materials and Methods: For all these reasons, we conducted a narrative review of the literature, and we focused on metabolic dysfunction related to MAFLD, with a special regard for cholesterol metabolism. Results: MAFLD is a recently redefined condition that better describes the metabolism derangement responsible for fatty liver disease. This distinguishes MAFLD from NAFLD. In fact, the diagnostic criteria for MAFLD require the presence of liver steatosis together with at least one of the following: obesity, T2DM, or evidence of metabolic disorder such as hypertriglyceridemia, low high-density lipoprotein cholesterol, or hypertension. As a result, MAFLD is closely linked to an increased cardiometabolic risk. Current therapeutic approaches can be used to reduce this risk, focusing on lifestyle interventions and pharmacological strategies. Several treatments in patients diagnosed with MAFLD are mainly cholesterol-lowering remedies. Among these, Pro-protein Convertase Subtilisin/Kexin type 9 inhibitors (PCSK9i) show the most promising efficacy profile but data on liver fibrosis are lacking. Agonists of GLP-1 receptor, Sodium-glucose cotransporter-2 inhibitors (SGLT2i) and Dipeptidyl Peptidase-4 inhibitors (DPP-4i) have a “ multi-hit “ action allowing their use also in diabetic patients with MAFLD. Conclusions: Lifestyle modifications, some nutraceuticals, statins, incretins, and PCSK9i have changed the natural course and significantly improved the cardiometabolic outcomes of MAFLD. Emerging cholesterol-lowering drugs, such as Bempedoic acid, can overcome low compliance to statins’ use and their controversial effect on liver fibrosis. Finally, medications targeting insulin resistance allow for strategic interventions of the convoluted pathophysiology of MAFLD in multiple steps, with the potential to reduce liver steatosis, inflammation, and necrosis and, sometimes even to reverse liver fibrosis.